2009
DOI: 10.1038/ejhg.2009.89
|View full text |Cite
|
Sign up to set email alerts
|

Impact of BRCA1 and BRCA2 variants on splicing: clues from an allelic imbalance study

Abstract: Nearly one-half of BRCA1 and BRCA2 sequence variations are variants of uncertain significance (VUSs) and are candidates for splice alterations for example, by disrupting/creating splice sites. As out-of-frame splicing defects lead to a marked reduction of the level of the mutant mRNA cleared through nonsense-mediated mRNA decay, a cDNA-based test was developed to show the resulting allelic imbalance (AI). Fifty-four VUSs identified in 53 hereditary breast/ovarian cancer (HBOC) patients without BRCA1/2 mutation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
1
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 43 publications
1
31
1
1
Order By: Relevance
“…For example, the GTAA deletion of intron 20 of the ATM gene promotes the exonization of a cryptic exon (46). However, other authors have suggested a minor role for such mutations in the molecular spectrum of BRCA1/2 (47).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the GTAA deletion of intron 20 of the ATM gene promotes the exonization of a cryptic exon (46). However, other authors have suggested a minor role for such mutations in the molecular spectrum of BRCA1/2 (47).…”
Section: Discussionmentioning
confidence: 99%
“…However, when BRCA mRNAs from tumors bearing such unclassified variants are analyzed, they often show splicing alterations. [76][77][78][79][80][81][82] Further mechanistic analyses have revealed that such unclassified variants are directly responsible for splicing alterations. For example, several unclassified variants in BRCA1 exon 18 induce exon skipping by altering the binding of splicing factors that enhance (SF2/ASF) or inhibit (hnRNP A1 and hnRNP H/F) exon 18 recognition.…”
Section: Widespread Alteration Of Splicing In Cancermentioning
confidence: 99%
“…The simultaneous detection of point mutations and large rearrangements is another advantage. However promoter regions are not covered and this must be taken into account, since deletions of the promoter regions are a probably rare but significant cause of HBOC (Brown, et al, 2002;Caux-Moncoutier, et al, 2009). Although technical performance was acceptable, the complexity of the currently available Emmalys interface prevents routine use of large rearrangement detection.…”
Section: Emmamentioning
confidence: 99%